2011
DOI: 10.1007/s11255-011-9983-0
|View full text |Cite
|
Sign up to set email alerts
|

Causes of autonomic dysfunction in idiopathic recurrent kidney stone formers

Abstract: Several factors may contribute to the presence of autonomic dysfunction in patients with recurrent nephrolithiasis. This abnormality has significant implications in cardiovascular risk assessment and treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…What is interesting is that the recent study of Domingos and Escalda 15 revealed autonomic dysfunction even in recurrent kidney stone formers what contributed with higher HR and BP comparing to healthy controls. One of the important determinants of SNS hyperactivity is abnormal renal sodium excretion and activation of the renin-angiotensin-aldosterone system and then volume overloud, which per se may also play a role.…”
Section: Discussionmentioning
confidence: 93%
“…What is interesting is that the recent study of Domingos and Escalda 15 revealed autonomic dysfunction even in recurrent kidney stone formers what contributed with higher HR and BP comparing to healthy controls. One of the important determinants of SNS hyperactivity is abnormal renal sodium excretion and activation of the renin-angiotensin-aldosterone system and then volume overloud, which per se may also play a role.…”
Section: Discussionmentioning
confidence: 93%
“…CKD as well as older age is characterized by elevated sympathetic nerves system activity, which correlates with increased vascular resistance and systemic BP and leads to CVD. Sympathetic nerves system overactivity in renal patients also aggravates kidney failure progression 46…”
Section: Introductionmentioning
confidence: 99%